2021
DOI: 10.1186/s12936-021-03976-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long-lasting insecticidal nets (LLINs) physical integrity on utilization

Abstract: Background In Ethiopia, despite improvements in coverage and access, utilization of long-lasting insecticidal nets (LLINs) remains a challenge. Different household-level factors have been identified as associated with LLIN use. However, the contribution of LLIN physical integrity to their utilization is not well investigated and documented. This study aimed to assess the association between the physical integrity of LLINs and their use. Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
2
6
0
1
Order By: Relevance
“… 48 The loss of physical integrity of LLINs will impact the use of the nets as shown in a study in Ethiopia where damaged LLINs were less commonly used. 17 Also, torn nets are used for other purposes in Burundi and are no longer kept in the houses (WVB and CL, personal observations), further decreasing LLIN use. Studies in different African settings also showed that the effective lifespans of LLINs in the field are often shorter than 3 years, and rather depends on local conditions (influenced by living conditions and local behaviour of net maintenance that impact damage) than related to a specific LLIN brand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 48 The loss of physical integrity of LLINs will impact the use of the nets as shown in a study in Ethiopia where damaged LLINs were less commonly used. 17 Also, torn nets are used for other purposes in Burundi and are no longer kept in the houses (WVB and CL, personal observations), further decreasing LLIN use. Studies in different African settings also showed that the effective lifespans of LLINs in the field are often shorter than 3 years, and rather depends on local conditions (influenced by living conditions and local behaviour of net maintenance that impact damage) than related to a specific LLIN brand.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the fast decline of the LLINs effect, before the three full years of expected lifespan, in the highland setting of Burundi might be multiple and related to the fast loss of physical integrity of the nets 48. The loss of physical integrity of LLINs will impact the use of the nets as shown in a study in Ethiopia where damaged LLINs were less commonly used 17. Also, torn nets are used for other purposes in Burundi and are no longer kept in the houses (WVB and CL, personal observations), further decreasing LLIN use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penggunaan kelambu, terutama kelambu berinsektisida (long-lasting insecticidal nets/LLINs) cukup efektif untuk mencegah penularan malaria serta dapat diterima oleh masyarakat 13 . Kampanye penggunaan kelambu serta pembagian kelambu berinsektisida perlu disertai dengan penyuluhan tentang perawatan kelambu yang digunakan agar kelambu tetap efektif dalam mencegah penularan malaria [14][15][16] . Hasil penelitian di Sumatera Selatan mendapatkan bahwa masyarakat banyak yang menggunakan kelambu untuk mencegah gigitan nyamuk meskipun dengan cara membeli sendiri sehingga kelambu yang digunakan adalah kelambu yang tanpa insektisida 5 .…”
Section: Tabel 6 Distribusi Responden Berdasarkan Pencegahan Penulara...unclassified
“…Children under ve years of age and women of reproductive age are consistently prioritized for ITN use, particularly when households don't have enough ITNs, with adolescents (especially boys) the least prioritized [15]. The condition of an ITN, related to its age and the development of holes and tears, is associated with early discarding of ITNs and therefore lack of use [16][17][18][19]; the decay rate of ITNs is a critical component of overall trends in ITN access, determining how quickly coverage declines following mass distribution campaigns and other large-scale distributions [2,5]. Pulford et al [6] reviewed 22 available studies in 2011 for reasons why nets went unused, nding that discomfort due to heat and perceived low risk of malaria due to low mosquito density were the primary reasons cited, but noted that ndings were tentative given the dearth of published studies.…”
Section: Introductionmentioning
confidence: 99%